Evaluating a multi-panel air cathode through electrochemical and biotic tests. (1st January 2019) - Rossi, Ruggero; Jones, David; Myung, Jaewook; Zikmund, Emily; Yang, Wulin; Gallego, Yolanda Alvarez; Pant, Deepak; Evans, Patrick J.; Page, Martin A.; Cropek, Donald M.; Logan, Bruce E.
Abstract: To scale up microbial fuel cells (MFCs), larger cathodes need to be developed that can use air directly, rather than dissolved oxygen, and have good electrochemical performance. A new type of cathode design was examined here that uses a "window-pane" approach with fifteen smaller cathodes welded to a single conductive metal sheet to maintain good electrical conductivity across the cathode with an increase in total area. Abiotic electrochemical tests were conducted to evaluate the impact of the cathode size (exposed areas of 7 cm 2, 33 cm 2, and 6200 cm 2 ) on performance for all cathodes having the same active catalyst material. Increasing the size of the exposed area of the electrodes to the electrolyte from 7 cm 2 to 33 cm 2 (a single cathode panel) decreased the cathode potential by 5%, and a further increase in size to 6200 cm 2 using the multi-panel cathode reduced the electrode potential by 55% (at 0.6 A m −2 ), in a 50 mM phosphate buffer solution (PBS). In 85 L MFC tests with the largest cathode using wastewater as a fuel, the maximum power density based on polarization data was 0.083 ± 0.006 W m −2 using 22 brush anodes to fully cover the cathode, and 0.061 ± 0.003 W m −2 with 8 brush anodes (40% of cathode projected area) compared to 0.304 ± 0.009 W m −2 obtained in the 28 mL MFC. Recovering power from large MFCs will therefore be challenging, but several approaches identified in this study can be pursued to maintain performance when increasing the size of the electrodes. Graphical abstract: Highlights: Window-pane 0.62 m 2 cathode successfully installed in 85 L MFC. The large 15-panel cathode had lower abiotic performance than smaller cathodes. Power density of 0.083 ± 0.006 W m −2 was obtained using wastewater as a fuel. Maintaining full coverage of the electrodes maximized the power production.